2021
DOI: 10.1021/acs.jmedchem.1c00160
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Tacrine–Pyrimidone Hybrids as Potent Dual AChE/GSK-3 Inhibitors for the Treatment of Alzheimer’s Disease

Abstract: Based on a multitarget strategy, a series of novel tacrine−pyrimidone hybrids were identified for the potential treatment of Alzheimer's disease (AD). Biological evaluation results demonstrated that these hybrids exhibited significant inhibitory activities toward acetylcholinesterase (AChE) and glycogen synthase kinase 3 (GSK-3). The optimal compound 27g possessed excellent dual AChE/GSK-3 inhibition both in terms of potency and equilibrium (AChE: IC 50 = 51.1 nM; GSK-3β: IC 50 = 89.3 nM) and displayed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…As part of this approach, the dual inhibition of acetylcholinesterase (AChE) and GSK-3 was predicted to produce beneficial effects by preventing acetylcholine decline and the toxic effect of hyperactive GSK-3 (Zhang et al, 2019). Strategic design was employed to incorporate two distinct pharmacophores thought to be important for the inhibition of AChE and GSK-3, and the result was tacrine-pyrimidone hybrid compounds (Yao et al, 2021). The chosen compound, 27g, entered the brain in vivo, and provided neuroprotection against glyceraldehyde-induced neurite damage in cells, and scopolamine-induced cognition-impairment (Yao et al, 2021).…”
Section: Neurodegenerative Diseases Alzheimer's Disease and Other Tauopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this approach, the dual inhibition of acetylcholinesterase (AChE) and GSK-3 was predicted to produce beneficial effects by preventing acetylcholine decline and the toxic effect of hyperactive GSK-3 (Zhang et al, 2019). Strategic design was employed to incorporate two distinct pharmacophores thought to be important for the inhibition of AChE and GSK-3, and the result was tacrine-pyrimidone hybrid compounds (Yao et al, 2021). The chosen compound, 27g, entered the brain in vivo, and provided neuroprotection against glyceraldehyde-induced neurite damage in cells, and scopolamine-induced cognition-impairment (Yao et al, 2021).…”
Section: Neurodegenerative Diseases Alzheimer's Disease and Other Tauopathiesmentioning
confidence: 99%
“…Strategic design was employed to incorporate two distinct pharmacophores thought to be important for the inhibition of AChE and GSK-3, and the result was tacrine-pyrimidone hybrid compounds (Yao et al, 2021). The chosen compound, 27g, entered the brain in vivo, and provided neuroprotection against glyceraldehyde-induced neurite damage in cells, and scopolamine-induced cognition-impairment (Yao et al, 2021).…”
Section: Neurodegenerative Diseases Alzheimer's Disease and Other Tauopathiesmentioning
confidence: 99%
“…, using small therapeutic molecules. Most of the small molecules were synthesized using privileged scaffolds of medicinal importance such as pyrimidine, 31 pyrazine, 32 acridine, 33 triazolopyrimidine, 34,35 triazene, 36 coumarin, 37 chromones, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As related to medicinal chemistry, several studies were reported on the development of new inhibitors of known biological targets related to neurodegenerative diseases, such as acetylcholinesterase (AChE), 16,17 butyrylcholinesterase (BuChE), 18 glycogen synthase kinase 3 beta (GSK3β), 19 monoamine oxidase A and B (MAO-A and MAO-B), 20 plasma membrane redox enzymes, 21 etc., and disaggregation of misfolded proteins, 22,23 i.e., τ-protein, 24,25 amyloid-β (Aβ), 26,27 TAR DNA binding protein 43 (TDP-43), 28 α-synuclein, 29,30 etc., using small therapeutic molecules. Most of the small molecules were synthesized using privileged scaffolds of medicinal importance such as pyrimidine, 31 pyrazine, 32 acridine, 33 triazolopyrimidine, 34,35 triazene, 36 coumarin, 37 chromones, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The senile plaque (SP) generated by β -amyloid (A β ) and neurofibrillary tangles (NFTs) made of phosphorylated tau proteins in the hippocampus are considered as the main pathogenic etiologies of AD [ 10 ]. The pathological mechanism of AD is complex, and several hypotheses have been proposed, including cholinergic injury hypothesis [ 11 , 12 ], β -amyloid protein cascade hypothesis [ 13 ], tau protein hyperphosphorylation hypothesis [ 14 ], metal ion poisoning hypothesis [ 15 ], calcium imbalance hypothesis [ 16 ], chronic inflammation hypothesis [ 17 ], and oxygen free radical damage hypothesis [ 18 ]. Among these hypotheses, the cholinergic injury is the most widely accepted and its clinical effectiveness has been approved.…”
Section: Introductionmentioning
confidence: 99%